Effect of ammonia solution on the electrochemical properties of magnesium manganese oxide material for aqueous zinc-ion batteries - Wasim Akram Syed; Ashok Kumar Kakarla; Hari Bandi; R. Shanthappa; Jae Su Yu (Journal of Magnesium and Alloys)
Aqueous zinc (Zn)-ion batteries (AZIBs) have gained significant interest in energy storage due to several unique advantages. Utilizing water-based electrolytes enhances environmental sustainability, while the abundance and affordability of Zn offer economic benefits. Manganese (Mn)-based materials, commonly used as cathodes in these batteries, provide high theoretical capacity, high electrical conductivity, and good structural stability. However, these materials suffer from capacity degradation over repeated cycles due to structural collapse and limited conductivity. To address this problem, we synthesized a magnesium (Mg)- and Mn-based composite, Mg2+-Mn3O4, using the hydrothermal method with an optimized amount of ammonium hydroxide (NH4OH) solution. This approach effectively stabilizes the structure during cycling, enhancing both capacity retention and conductivity. The Zn2+/H+ intercalation/deintercalation process was confirmed by experimental results and ex-situ X-ray diffraction analysis, which demonstrates that Mg2+, along with optimized NH4OH amount, prevents structural collapse and improves conductivity. Under optimal process conditions, the composite electrode (Mg2+-Mn3O4–8 ml) achieved a capacity of 173.58 mA h g–1 at 0.5 A g–1, with excellent rate performance of 71.39 mA h g–1 at 10 A g–1. Remarkably, even at 5 A g–1, the electrode maintained a capacity of 86.87 mA h g–1 over 2100 cycles, underscoring the role of Mg2+ and NH4OH in enhancing the reversible insertion/extraction stability of Zn2+ in Mn-based layered materials. This study presents a novel strategy for metal-ion incorporation in Mn-based AZIBs, offering insights into the optimization of cathode materials and advancing research on associated storage mechanisms.